Droplet detachment behavior from a rough hydrophilic surface. (January 2020) - Wang, C.T.; Leung, W.T.; Xu, J.C.; Fu, S.C.; Chao, Christopher Y.H.
Abstract: Understanding of the droplet detachment behavior from rough hydrophilic surfaces is important in many biological and industrial applications such as biomedicine, surface coating, and pathogen-laden aerosol resuspension. Due to the partial detachment of the droplet on hydrophilic surfaces, leaving behind some droplet residues, the adhesion behavior is extremely complicated. Here we reveal a new adhesion mechanism between a droplet and a rough hydrophilic surface. The adhesion behavior is controlled by a liquid film stuck in the surface microstructure. We establish a model to describe the contributions of liquid film and naked solid peaks, to the work of adhesion and verify the model experimentally. We also find that the normal adhesion force is about 3.35 ± 0.25 times of the lateral adhesion force for different surface roughness, meaning that the separation direction is an important factor affecting adhesion due to the different separation mechanisms. The results of this work shed new insights on the understanding of droplet detachment and adhesion to a rough surface. Highlights: Rough surface attaches larger liquid aerosol than smooth surface, while rough surface holds smaller solid aerosol. A model is proposed and experimentally verified to reveal adhesion mechanism of a liquid aerosol to a rough surface. Normal adhesion force is about 3.35±0.25 times of lateral adhesion force, which is independent of surface roughness.